2016
DOI: 10.1124/dmd.116.073320
|View full text |Cite
|
Sign up to set email alerts
|

Species Differences in Human and Rodent PEPT2-Mediated Transport of Glycylsarcosine and Cefadroxil in Pichia Pastoris Transformants

Abstract: The proton-coupled oligopeptide transporter PEPT2 (SLC15A2) plays an important role in the disposition of di/tripeptides and peptide-like drugs in kidney and brain. However, unlike PEPT1 (SLC15A1), there is little information about species differences in the transport of PEPT2-mediated substrates. The purpose of this study was to determine whether PEPT2 exhibited a species-dependent uptake of glycylsarcosine (GlySar) and cefadroxil using yeast Pichia pastoris cells expressing cDNA from human, mouse, and rat. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…However, PEPT1 and PEPT2 show opposite affinities for GlySar, with mM values of K m for PEPT1 and μM values of K m for PEPT2. 38,39 Our kinetic analysis of GlySar uptake indicated hPHT1 was a low affinity transporter (K m = 1.69 ± 0.30 mM), whose transport activity was similar to PEPT1. However, Bhardwaj et al reported that the uptake of GlySar was not different in COS-7 transiently transfected with wildtype hPHT1 or vector.…”
Section: Molecular Pharmaceuticsmentioning
confidence: 94%
“…However, PEPT1 and PEPT2 show opposite affinities for GlySar, with mM values of K m for PEPT1 and μM values of K m for PEPT2. 38,39 Our kinetic analysis of GlySar uptake indicated hPHT1 was a low affinity transporter (K m = 1.69 ± 0.30 mM), whose transport activity was similar to PEPT1. However, Bhardwaj et al reported that the uptake of GlySar was not different in COS-7 transiently transfected with wildtype hPHT1 or vector.…”
Section: Molecular Pharmaceuticsmentioning
confidence: 94%
“…Human data were obtained from the literature (Garrigues et al, 1991); hu, humanized PepT1 mice. species in drug capacity (V max ) and affinity (K m ) of related transporters (Hu et al, 2012;Song et al, 2017). Humanized mouse models have been developed in an attempt to improve the predictability of pharmacokinetics, metabolic contributions, drug toxicity, and receptor response when translating results from animals to human subjects (Katoh et al, 2004;Gonzalez and Yu, 2006;Scheer and Roland Wolf, 2013;Scheer and Wilson, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…[ 14 C]Oseltamivir was employed as well revealing it is not a substrate for PEPT1. [ 3 H]GlySar uptake and [ 3 H]Cefadroxil uptake were investigated for hPEPT2 [ 211 ].…”
Section: Current Methodology For Purification and Functional Studies ...mentioning
confidence: 99%